2003
DOI: 10.3171/jns.2003.99.1.0047
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of moderate hypothermia in patients with severe head injury and intracranial hypertension refractory to mild hypothermia

Abstract: The authors concluded that moderate hypothermia is not effective in improving clinical outcomes in severely head injured patients whose ICP remains higher than 40 mm Hg after treatment with mild hypothermia combined with conventional therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…However, Marion et al found that hypothermia was associated with a significant reduction in CBF, with a mean of 28.8 ml/100 gr/min in the cooled group and 35.7 ml/100 gr/min in the normothermia group [53]. Shiozaki et al documented a mean decrease of 15.4 ml/100 gr/min in CBF (from approximately 35 to 20 ml/100 gr/min) associated with cooling to 34°C [89]. In their study of 24 TBI patients with intact pressure autoregulation, cooling to 34°C was not found to disrupt autoregulation, crudely determined as the response of ICP to changes in blood pressure.…”
Section: Pathophysiologic Basis For Hypothermia Effectmentioning
confidence: 94%
See 1 more Smart Citation
“…However, Marion et al found that hypothermia was associated with a significant reduction in CBF, with a mean of 28.8 ml/100 gr/min in the cooled group and 35.7 ml/100 gr/min in the normothermia group [53]. Shiozaki et al documented a mean decrease of 15.4 ml/100 gr/min in CBF (from approximately 35 to 20 ml/100 gr/min) associated with cooling to 34°C [89]. In their study of 24 TBI patients with intact pressure autoregulation, cooling to 34°C was not found to disrupt autoregulation, crudely determined as the response of ICP to changes in blood pressure.…”
Section: Pathophysiologic Basis For Hypothermia Effectmentioning
confidence: 94%
“…They argue this not only based on their own clinical experience but also based on their observation that patients with large contusions typically have disruption of the blood-brain barrier and loss of autoregulation. Others have found that patients with severe diffuse swelling are not likely to respond to hypothermia, and in one study of eight patients with very high ICPs (>40 mm Hg) and diffuse swelling, all eight died within 48 h of injury despite therapeutic hypothermia to 31°C [89]. Studies are needed to refine the pathophysiologic characterization of injuries with the use of serum or CSF biomarkers [51], and this should enable even better matching of injury type with effective treatments.…”
Section: Future Considerations For Therapeutic Hypothermia In Tbimentioning
confidence: 96%
“…It is possible that if a patient fails to improve with pharmacologic metabolic suppression, there may not be any further improvement following induction of hypothermia, although it may act synergistically when a response is seen. If hypothermia is applied in the setting of refractory elevations in ICP, further reduction in temperature beyond 32°C has not been shown to impart further effi cacy, and more complications may be encountered [50]. However, if recurrent elevations in ICP are encountered during rewarming, slowing the rate of rewarming or extending the duration of hypothermia may be necessary.…”
Section: Therapeutic Hypothermia and Temperature Augmentationmentioning
confidence: 95%
“…However, three cases of severe pneumonia were seen in the mild hypothermia group but not in the very mild hypothermia group (Hayashi et al, 2005). Shiozaki et al (2003) determined whether moderate hypothermia (318C) improves clinical outcome in patients with SHI whose intracranial hypertension cannot be controlled using mild hypothermia (348C). Twenty-two consecutive patients with SHI who fulfilled the following criteria were included in this study: an ICP that remained higher than 40 mm Hg despite the use of mild hypothermia combined with conventional therapies; and a GCS score of 8 or less on admission.…”
Section: Mild-to-moderate Hypothermiamentioning
confidence: 99%